Planejamento físico financeiro por meio de sistemas de fluxo de trabalho e tecnologia BIM - Sérgio Geraldo dos Reis Júnior (2020)
Civil construction has large gaps in terms of constructive methods, management and productivity. Many countries, including Brazil, are investing in new management methods, aiming to complete future projects on time and budget. This research are aligned with these objects, as the main objective of this paper is to introduce new practices for a better way to manage, control and monitor construction projects, materializing this strategis in a unique cost and progress schedule. To identify benefits in vertical building projects, a case study was run to analyze the planning construction proposed for the renovation of the Engineering Schoool of the Federal University of Minas Gerais (UFMG). Two new schedules were created, using location based technique and Building Information Modeling (BIM) technology and then, they were compared with the existing one. As result, the tasks were planned more reliably, avoiding team interferences and decreasing gaps of costs and progress. Futhermore, a database was created with the use of BIM softwares, becoming possible to create a better strategy to control and monitor the project construction.